2018
DOI: 10.1016/j.ijsu.2018.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Mini vs Roux-en-Y gastric bypass: A meta-analysis and systematic review

Abstract: Mini gastric bypass seems to be a simpler procedure with a better weight reduction effect. This seems to also be the case regarding remission rates of type 2 diabetes mellitus when using Mini gastric bypass in comparison to Roux-en-Y gastric bypass. A small sample size and biased data may have influenced the stability of our results. In light of this, surgeons should treat our results in a conservative way. Larger sample size and multi-center randomized control trials are needed to compare the effectiveness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
41
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 44 publications
2
41
0
2
Order By: Relevance
“…The estimated blood loss was 50.7 (0-100) ml, similar to that in another study (mean 39.8 ml) [22]. The postoperative hospital stay was 1.9 (1-4) days, which seems shorter than that in other studies (about 2-7.1 days) [14]. In several studies, the simplified surgical processes of LMGB resulted in a shorter operative time, less blood loss, and shorter hospitalization than LRYGB [22][23][24].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The estimated blood loss was 50.7 (0-100) ml, similar to that in another study (mean 39.8 ml) [22]. The postoperative hospital stay was 1.9 (1-4) days, which seems shorter than that in other studies (about 2-7.1 days) [14]. In several studies, the simplified surgical processes of LMGB resulted in a shorter operative time, less blood loss, and shorter hospitalization than LRYGB [22][23][24].…”
Section: Discussionsupporting
confidence: 83%
“…In terms of the impact of LMGB on comorbidities, our study showed that 3 of 4 (75%) patients had remission of [14].…”
Section: Discussionmentioning
confidence: 72%
“…11 Increasingly, evidence reveals that the risk of long-term complications of MGB is less and that the metabolic effects are better than Roux-en-Y gastric bypass. 12,13 A meta-analysis published by Wang et al showed that MGB has multiple advantages over Roux-en-Y gastric bypass. 13 These advantages are a higher 1-year excess weight loss (EWL), higher 2-year EWL, higher type II DM remission rate, and a shorter operation time.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 A meta-analysis published by Wang et al showed that MGB has multiple advantages over Roux-en-Y gastric bypass. 13 These advantages are a higher 1-year excess weight loss (EWL), higher 2-year EWL, higher type II DM remission rate, and a shorter operation time. In terms of long-term results, such as %EWL and type II DM remission, MGB might be superior to laparoscopic SG also.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation